Individualism-collectivism : A comparative study of Malaysian and Australian managers / Fauziah Noordin - Noordin, Fauziah (Universiti Teknologi MARA Cawangan Pahang, 2004)
The purpose of this study is to examine the level of individualismcollectivism of managers in Malaysia and Australia. This study revealed that there are significant differences between Malaysian and Australian managers on the levels of vertical individualism, horizontal collectivism, and vertical collectivism. The results of this study may be of interest and assistance to managers of multinational and international organizations who need to manage in global contexts and, therefore, need to understand cultural-driven differences in personal and interpersonal work-related conditions between and across nations. The implications of the study findings to organizations and directions for future research are also discussed.